China's Cyber Warfare The Evolution of Strategic Doctrine - Fritz, Jason R. 1977 (Lexington Books, 2017)
"Chinese government policies have drawn international criticisms including persistent allegations of online espionage, domestic Internet censorship, and an increased military capability utilizing computer networks. This book analyzes the strategic context, conceptual framework, and historical evolution of China's cyber warfare doctrine."--Provided by publisher